(untitled) (Prilozi za orijentalnu filologiju, 2021)
The paper examines the possible connection of the Ottoman princess Esma with the construction of a mosque in Jajce, which, as recorded in folklore, she had built by donating her jewelry. In this regard, information is provided about the princess herself, as well as her husband, Grand Vizier Muhsinzada Mehmed-pasha, who once held the position of vali of the Bosnian eyalet, and the waqfs they left in both Bosnia and Istanbul.